Strategic workload management in digital business: Lessons from a case study on internet service provider company - Kristinawati, Didin; Ghalib, Ghalib Kamal (Nur Science Institute, 2025)
This study aims to analyze workload distribution at ISPCX, a leading internet service provider in Bandung, to identify imbalances and propose strategies for optimizing resource allocation and operational efficiency. The study employs a single-case study approach, integrating both quantitative and qualitative methods. Data were collected through document analysis, employee surveys, semi-structured interviews, and direct observations. The Full-Time Equivalent (FTE) method was utilized to calculate workload ratios, providing a quantitative measure of workforce utilization. The analysis revealed significant workload disparities across roles and divisions. Overburdened roles, such as the Manager in the General Affairs Division (workload ratio 3.24), risk employee burnout. Conversely, underutilized roles in the Technical Division, like the Manager (0.30), indicate inefficiencies in task alignment. Balanced roles were observed in specific administrative positions, highlighting potential best practices. The findings underscore the importance of strategic task redistribution and leveraging digital tools to improve efficiency and reduce employee strain. This study provides actionable insights for digital businesses, emphasizing the role of evidence-based workload management in driving economic growth and sustainable development.